The Plant Regulator Soaking Seeds and its Reflections on Growth and Yield Quality of Wheat - Khursheed, Mohammed Q.; Saber, Trifa Z.; Hassan, Tara M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
A greenhouse pot experiment was carried out during November 2013 to May 2014. Winter wheat grains (Triticum aestivum L.), cultivars Abu-Ghureb and Cham6 were used to investigate the effect of soaking seeds in 300ppm of benzyl adenine (BA) or daminozide solutions for 6 hours before sowing vegetative, yield components, leaf chlorophylls and some chemical constituents of seeds. BA treatment led to significant increases in tiller number plant-1, chlorophyll b, P, dry gluten, N and protein contents of seeds. It also led to significant decreases in number of leaves plant-1. In addition, the number of tillers plant-1, shoots dry weight plant-1, P, N and protein contents of seeds were increased by daminozide treatment, but this caused a significant decrease in the plant height, number of leaves plant-1 and flag leaf area. Number of grains plant-1, weight of 1000 grains and grains yield were significantly increased by both treatments. Cultivar variability was noted for some tested parameters. The tall, N, P content and protein content of Abu-Ghureb cultivar were higher significantly than Sham6. The case was opposite with number of leaves plant-1, flag leaf area, shoots dry weight plant-1, spike length and grain number plant-1.